Functional Diagnostics of Arterial Vessels by Pulse Wave Analysis and Equipment for Its Implementation - Usanov, D. A.; Skripal, An. V.; Brilenok, N. B.; Dobdin, S. Yu; Averianov, A. P.; Bakhmetev, A. S.; Baatyrov, R. T. (Biomedical engineering, 2020)
The results of screening of the arterial system based on pulse waveform measurement by the oscillometric method are presented. Tests were performed in a group of students from the Saratov State National Research University. The muscle tone response to the occlusion of the brachial artery was studied to assess endothelial dysfunction. Of the 71 subjects examined, 65 subjects (92%) responded to the artery occlusion with an increase in the parameter P 3 proportional to the second time derivative of the pulse waveform. Six subjects (8%) responded to the artery occlusion with a decrease in P 3 indicative of endothelial dysfunction. The test results were confirmed using the duplex ultrasonography screening of the arteries of the upper limbs. The equipment used to implement the suggested diagnostic technique is described.